Production of Cassava Syrup with Glucoamylase Immobilised to Acid-washed Charcoal - Ba'i, Subhi; Mohd Ghazali, Hasanah (1986)
Glucoamylase immobilised to acid-washed animaL charcoaL was used to effect the saccharification of Liquefied cassava starch. A 7 DE Liquefied cassava starch solution (30% D. S.) was converted into a 69 DE cassava syrup when the substrate was fed at a ]low rate of 1. 0 mL min }into a packed- bed coLumn reactor of immobilized glucoamyLase. The relationship between the ]low-rate and the extent of saccharification was found to be asymptotic. Much of the brown coLour that deveLoped during the Liquefaction of the substrate was removed when the flow rates was Low, giving a fairly colorless syrup.